Answer:
3
Step-by-step explanation:
g(-1) means what is g(x) when x=-1.
So find -1 under the column labeled x and then scroll directly to the right of that and you should see what g(-1). It is 3
Here are my examples:
g(-8)=6
g(-5)=-2
g(-1)=3
g(0)=-5
Answer:
A
Step-by-step explanation:
It resluts in 4
Answer:
8
Step-by-step explanation:
Substitute 3 for x
-2x + 14
-2(3) + 14
-6 + 14 = 8
Answer:
5(4 + 4)
Step-by-step explanation:
5(4 + 4)
20 + 20
40
Hope this helps!
=)
Answer:
∠X in the pre-image will be equal to ∠L in the main image
Step-by-step explanation:
△LMN is the result of a reflection of △XYZ which means △LMN is the mirror image △XYZ
hence, the left of △XYZ will be equivalent to the right of △LMN and the right of △XYZ will be equivalent to the left of △LMN
Hence, ∠X in the pre-image will be equal to ∠L in the main image